THE NURSERY SCHOOL: IDENTITY AT STAKE - Patricia Sarlé (Universidad Nacional del Nordeste, 2019)
Play has always had a meaningful place within the pedagogical discourse, specifically in early childhood education. However, in everyday practice, it would appear as a secondary aspect, that loses strength as the child grows. It states its educational value and the need to think about teaching based on playing, nevertheless, it is still considered that play is free spontaneous for a child, in fact, it arises naturally, whatever the social context or available materials. The play scenario is a territory in which the educator cannot enter without failing in their attempt. Therefore, the intention of this work is to put into discussion the metaphor of play as "hinge". With this in mind, we are considering the play as that "joint axis" among the different scenarios that are involved in kindergarten everydayness. Therefore, we could say that the game is a meeting point among the historical path of the early school; the curriculum subjects; the different processes involved in the school, and the contents and the way of teaching. Past and present of the early school, educators and children, learning and teaching, school culture and children´s culture, toughen up the perspective with which we look up on the playful phenomenon that tries to articulate them and allows us to jump up to a new level of conceptualization. In this way, play is based on a new teaching practices model of analysis in the early school and a pivot to encourage identity processes within children early education area.